The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/infdis/jit295
|View full text |Cite
|
Sign up to set email alerts
|

Route of Sexual Exposure Is Independently Associated With Seropositivity to HPV-16 and HPV-18 Among Clients of an STI Clinic in the Netherlands

Abstract: We investigated the route of sexual exposure as a determinant for human papillomavirus (HPV)-16 and HPV-18 seropositivity. At the Amsterdam sexually transmitted infections clinic we recruited 4 risk groups: (1) men who have sex with women only (MSW; n = 751); (2) women who have sex with men (WSM; n = 749); (3) men who have sex with men (MSM) reporting insertive anal sex only (insMSM; n = 156); and (4) MSM reporting receptive anal sex (recMSM; n = 415). In multivariable analyses, HPV-16 seropositivity was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 11 publications
2
21
0
Order By: Relevance
“…Previous studies observed that HPV seropositivity was positively associated with type-specific anal HPV infection rather than with genital (penile) HPV infection [20][22]. Also, seropositivity was higher among HIV-positive than HIV-negative MSM [23].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies observed that HPV seropositivity was positively associated with type-specific anal HPV infection rather than with genital (penile) HPV infection [20][22]. Also, seropositivity was higher among HIV-positive than HIV-negative MSM [23].…”
Section: Introductionmentioning
confidence: 85%
“…If seroconversion does occur, antibodies may persist for many years [15]. Seropositivity is thought to be associated with persistent HPV infection, HPV viral load, and anatomical site of infection [13], [16][22].…”
Section: Introductionmentioning
confidence: 99%
“…The positive association of the increasing number of male anal sex LTP with the seropositivity of HPV is also consistent with previous studies [20, 35] and is likely to be explained by i) the increased probability of exposure to HPV types due to multiple sex partners, ii) the highest DNA prevalence of HPV infection and persistence in the anal canal of MSM, and iii) the anatomic site-specific immune response. Studies have shown that HPV infection is common in the anal canal, and its prevalence is higher among MSM than men who have sex with women (MSW) [3537]. Recently, emerging evidence showed that HPV infection persists longer in the anal canal of MSM [38] which may explain the highest incidence of HPV-related anal cancers in MSM [39].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the cross-sectional correlation between detection of HPV DNA and type-specific antibodies is poor (9,26). However, recent data suggest that the anatomic site of HPV infection could influence seropositivity (12,27,28); mucosal (e.g., anal) infections might be more likely to elicit a humoral immune response than infections in keratinized epithelium (e.g., the penile shaft). In addition, it has been observed that persistent, rather than transient, HPV infection is associated with seroconversion (5,9,29).…”
Section: Discussionmentioning
confidence: 99%